Antiprotozoal activity of the cyclopalladated complexes against leishmania amazonensis and trypanosoma cruzi - Velásquez, Angela M. A. [UNESP]; De Souza, Rodrigo A. [UNESP]; Passalacqua, Thaís G. [UNESP]; Ribeiro, Aline R.; Scontri, Mateus [UNESP]; Chin, Chung M. [UNESP]; De Almeida, Leticia [UNESP]; Cistia, Mayara L. Del [UNESP]; Rosa, João A. Da [UNESP]; Mauro, Antonio E. [UNESP]; Graminha, Marcia A. S. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2016)
The present study describes the antiprotozoal activities of four cyclopalladated compounds, [Pd(dmba)(μ-Cl)]2 , [Pd(dmba)(NCO)(isn)], [Pd(dmba)(N3)(isn)] and [Pd(dmba)(μ-NCO)]2 , (dmba: N,N'-dimethylbenzylamine and isn: isonicotinamide), against the diseases leishmaniasis (Leishmania amazonensis and Leishmania infantum), Chagas disease (Trypanosoma cruzi) and human African trypanosomiasis (Trypanosoma brucei). [Pd(dmba)(μ-NCO)]2 exhibited good leishmanicidal and trypanocidal activities against L. amazonensis and T. cruzi intracellular amastigote forms, with a 50% inhibitory concentration (IC50 ) value of less than 9 μM and selectivity indexes of 14.47 and 28.42, respectively. Stability essays were conducted in phosphate buffer saline (PBS) pH 7.0 and showed that [Pd(dmba)(μ-NCO)]2 is the most stable molecule. These findings indicate that this compound presented higher selectivity for these parasites than the other tested compounds. The data presented here suggest that this compound should be considered in the development of new and more potent drugs for the treatment of leishmaniasis and Chagas disease.
Keywords: Chagas disease; Cyclopalladated; Leishmania amazonensis; Leishmaniasis; Trypanosoma cruzi; Trypanosomiasis